DEVELOPMENT OF POP-UP BOOK MEDIA IN THEMATIC LEARNING IN GRADE III SDN 101921 BERINGIN - permata, lisa; Nuri Ramadhan; Syarifah Ainun Harahap (CV. Mitkom Indotama, 2024)
This study aims to: (1) produce Pop-Up Book learning media in the Thematic learning of food production technology development material in grade III SD Negeri 101921 Beringin, (2) find out the feasibility and practicality of Pop-Up Book learning media in the Thematic learning of food production technology development material in grade III SD Negeri 101921 Beringin which is valid from the results of feasibility validation by material experts, media experts, learning experts, and student responses. This research is a type of Research and Development (R&D) research with a 4D model developed by Thiagarajan (1974) which includes four steps, namely: the stages of define, design, development, and disseminate. The instruments used to collect data are interviews, documentation, and questionnaires. Based on the assessment of the validation results by material experts, 96% scores, media experts get 97.3% and learning experts get 93.3%, resulting in Pop-Up Book products that are very suitable for use for third grade elementary school students. Therefore, from the data from the validation results of the three validators, it can be concluded that the Pop-Up Book media in the Thematic learning of the Food Production Technology Development material was declared valid and there was no revision by experts, so it was declared very suitable to be used as a teaching material in learning.